Some observations in the dynamics of beams with intermediate supports - Albarracín, Carlos Marcelo (2004)
Several investigators have studied the influence of rotational and/or translational restraints at the ends of vibrating beams [1–17]. Kameswara Rao and Mirza [18] have derived exact frequency and normal mode shape expressions for uniform beams with ends elasticallyrestrained against rotation and translation. Nallim and Grossi [19] studied the dynamical behaviour of beams with complicating effects, such as non-uniform cross sections, presence of an arbitrarilyplaced concentrated mass and an axial force and ends elasticallyrestrained against rotation and translation.